2020
DOI: 10.11603/me.2414-5998.2020.2.11158
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Higher Education in the Formation of Students’ Healthy Lifestyle

Abstract: The article analyzes the problem of forming a healthy lifestyle of students. The current approach to deteriorating youth health encourages the search for new ways to generate positive motivation for a healthy lifestyle and scientific research. According to the literature data analysis, less than 15 % of students are considered healthy, 70 % of them have low and below-average levels of physical health, more than half (52.6 %) of them have different morphofunctional abnormalities, 36–40 % have chronic non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Temane studied college students’ opinions on the meaning of life in a university in South Africa through a questionnaire survey. They found that family expectations, education, and achievements were the most influential factors in understanding the meaning of lives ( Oliynyk et al, 2020 ). Al-Zoubi (2020) reported that LDE indeed provided help and change to college students.…”
Section: Related Workmentioning
confidence: 99%
“…Temane studied college students’ opinions on the meaning of life in a university in South Africa through a questionnaire survey. They found that family expectations, education, and achievements were the most influential factors in understanding the meaning of lives ( Oliynyk et al, 2020 ). Al-Zoubi (2020) reported that LDE indeed provided help and change to college students.…”
Section: Related Workmentioning
confidence: 99%